2019
DOI: 10.1097/sla.0000000000003657
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Damage Control Resuscitation

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 37 publications
1
57
0
2
Order By: Relevance
“…In post-trauma patients, aggressive resuscitation, as previously recommended, with crystalloid dilutes clotting factors and causes metabolic acidosis (hyperchloremic in the case of 0.9% NaCl administration) and interstitial edema. This also caused by microcirculation impairment and impaired oxygen tissue supply [46][47][48]. Colloids cause proteins to move from the blood to the interstitial space, therefore reducing plasma concentration of clotting factors, in particular of factor VII and von Willebrand factor, inhibiting platelet function, and reducing the interaction between factor XIII and fibrin polymers.…”
Section: Coagulopathy Associated With Resuscitation Maneuversmentioning
confidence: 99%
“…In post-trauma patients, aggressive resuscitation, as previously recommended, with crystalloid dilutes clotting factors and causes metabolic acidosis (hyperchloremic in the case of 0.9% NaCl administration) and interstitial edema. This also caused by microcirculation impairment and impaired oxygen tissue supply [46][47][48]. Colloids cause proteins to move from the blood to the interstitial space, therefore reducing plasma concentration of clotting factors, in particular of factor VII and von Willebrand factor, inhibiting platelet function, and reducing the interaction between factor XIII and fibrin polymers.…”
Section: Coagulopathy Associated With Resuscitation Maneuversmentioning
confidence: 99%
“…Severe bleeding in patients with trauma remains a challenge . Use of tranexamic acid (TXA), reduction of fluid expansion, high-ratio blood product transfusion, and expedient hemorrhage control have improved some patient outcomes, but mortality among patients with trauma and bleeding remains high due in part to trauma-induced coagulopathy . Trials of fixed ratio-based blood product transfusion, viscoelastic testing (VET) to guide a tailored combination of blood products, and a hybrid of the 2 approaches have provided a management evidence base for the trauma community, but no strategy has proven superior to another.…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhage is the leading cause of preventable death in civilian and battlefield traumatic injuries. 1,2 It has been reported that 60% of combat casualties resulted from massive bleeding and lack of effective treatment. In civilian traumatic injuries, massive bleeding is also the leading cause of death among people between 18 and 39, causing nearly 2 million deaths each year.…”
Section: Introductionmentioning
confidence: 99%